PENGEMBANGAN MODEL PENGELOLAAN SISTEM PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO YANG BERKELANJUTAN Studi Kasus PLTMH Kedungrong Desa Purwoharjo Kecamatan Samigaluh Kabupaten Kulon Progo Provinsi DI Yogyakarta - , ASPITA DYAH F ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Yogyakarta Province until 2014 has built a total of 10 (ten) micro hydropower plants (MHP). However, from these ten MHPs, there is only 1 (one) which is still in operation, namely Kedungrong Micro Hydropower Plant. This Kedungrong Micro Hydropower Plant was selected as the research area due to its success in managing the MHP so that the electricity generated can be used by its local residents until now. Based on this best practice, the other MHPs which are still under construction or that have âstalledâ should learn from Kedungrong Micro Hydropower Plant to be able to reoperate so that they will be sustainable. This research employed mixed methods, between the quantitative research method and the qualitative research method. First, the data were collected using surveys, interviews and observation and then the model of the management system that Kedungrong Micro Hydropower Plant applies was described and evaluated. The findings of the research suggest that a sustainable micro hydropower plant integrates three aspects, namely technical and environmental, social as well as economic aspects. The technical aspects deals with civil, mechanical and electrical components at the stages of planning, developing to operation and maintenance. The social aspects look carefully at community participation at the stages of planning, developing to operation and maintenance. Finally, the economic aspects pay attention to sources and forms of financing at the investment stage, the operation stage and the maintenance stage. In relation to the MHP scale, of those three aspects, the one that has the most significant impact on the sustainability of the MHP is the social aspects. Keywords : renewable energy, management model, sustainable MHP